Risk factors for colorectal cancer in Albania: a case-control study - Marsela Sina; Skerdi Prifti; Adea Kocollari; Ilir Akshija; Dorina Osmanaj; Gentiana Qirjako (Italian Journal of Medicine, 2025)
The prevalence of colorectal cancer (CRC) has increased significantly in recent years in many countries worldwide, including Albania, a transitional Mediterranean country in the Western Balkans. This study aimed to identify dietary patterns among CRC Albanian patients. This was a case-control study conducted during 2011-2016, including 262 patients histologically confirmed with a diagnosis of CRC and 289 sex- and age-matched controls who were family members of patients hospitalized for acute, non-neoplastic conditions unrelated to digestive tract diseases. Structured interviews employing standardized questionnaires were administered by trained personnel. Comparisons of dietary patterns were performed using the analysis of variance test for continuous variables and the χ² test for categorical variables. A dietary model characterized by a low intake of whole-grain bread, fruits, and olive oil was encountered more frequently among CRC patients. Our study indicates that diets rich in fruits, whole-grain bread, and olive oil exert a protective role against CRC development. The findings from this study are important for promoting protective diets, especially in areas with limited medical screening facilities.